Dukungan Keluarga dan Kualitas Hidup Lansia Hipertensi - I Wayan Suardana; Ni Luh Gede Intan Saraswati; Made Wiratni (Jurnal Gema Keperawatan, 2014)
This research has purpose to know about the correlation between family support and quality of life of elderly that suffered hypertension. This research is descriptive correlational research with use cross sectional approach. It has 59 samples using non probability technique with purposive sampling. To test the hypotesis, data is analyzed with Rank Spearman Test (p≤0,05). The result showed almost all of the elderlies have good family support in total of 27 elderlies (45,8%) and almost all of the elderlies have good quality of life in total 31 elderlies (52,5%). P value is 0,000 that means p less than 0,05 thus Ho is rejected and correlation coefficient value is 0,583 and that means there is correlation between family support and quality of life of elderly that suffered hypertension.